2018
DOI: 10.1038/s41433-018-0321-y
|View full text |Cite
|
Sign up to set email alerts
|

Teprotumumab, an insulin-like growth factor-1 receptor antagonist antibody, in the treatment of active thyroid eye disease: a focus on proptosis

Abstract: Thyroid eye disease is a disabling autoimmune disease associated with orbital inflammation and tissue remodeling which can result in significant proptosis, leading to visual alterations and is potentially sight threatening. Current evidence indicates that autoantibodies to the insulin-like growth factor 1 receptor (IGF-1R), along with the thyroid-stimulating hormone receptor (TSHR), mediate the pathogenesis in susceptible individuals. Teprotumumab, a monoclonal IGF-1R antagonist, has demonstrated previously in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
78
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(82 citation statements)
references
References 24 publications
3
78
0
1
Order By: Relevance
“…Efficacy in the fellow eye was similar to that in the study eye with regard to both proptosis and CAS improvement. The effects of teprotumumab appear to be durable as recent follow-up findings suggest that many responders experience sustained improvement, months following the treatment period (94). Thus, the results with teprotumumab are comparable to the best results thus far attained with surgical decompression (95).…”
Section: Insinuation Of Igf-ir Into the Pathogenesis Of Tao Has Resulmentioning
confidence: 77%
“…Efficacy in the fellow eye was similar to that in the study eye with regard to both proptosis and CAS improvement. The effects of teprotumumab appear to be durable as recent follow-up findings suggest that many responders experience sustained improvement, months following the treatment period (94). Thus, the results with teprotumumab are comparable to the best results thus far attained with surgical decompression (95).…”
Section: Insinuation Of Igf-ir Into the Pathogenesis Of Tao Has Resulmentioning
confidence: 77%
“…This study was particularly significant, as this is the first medical therapy that has demonstrated a reduction in proptosis. Douglas determined that patients with higher baseline proptosis had a greater response to teprotumumab than patients with lower baseline proptosis (mean reduction 3.7 vs. 2.6 mm) [53]. Further, there was improvement in proptosis in all gender-and smoking-stratified groups.…”
Section: Teprotumumabmentioning
confidence: 99%
“…Though IGF-1R is a widely expressed receptor, IGF-1R expression is increased on fibroblasts from the orbit, skin, and thyroid of patients with Graves' disease. The upregulation of IGF-1R and the TSHR in orbital fibroblasts has been proposed to lead to the accumulation of hyaluronan within orbital fat and muscle [10,53,54].…”
Section: Teprotumumabmentioning
confidence: 99%
“…Thyroid eye disease (TED) is a complex autoimmune disease characterized by orbital inflammation (active disease), with subsequent tissue remodeling and fibrosis when the disease becomes inactive 2,3. As TED progresses, it leads to proptosis, strabismus, corneal ulceration, and even optic neuropathy 2,4,5…”
Section: Introductionmentioning
confidence: 99%
“…Several treatment strategies are available, which focus on immune suppression 1. Though some provide short-term relief, they do not necessarily lead to disease course modification 2. The management of TED remains a major clinical and therapeutic challenge, as insufficient treatment can negatively impact patients’ quality of life (QoL) 2,6,7.…”
Section: Introductionmentioning
confidence: 99%